Managing Pregnancy in Autoimmune Disease with Fetal Anomaly: Ethical Challenges and Clinical Decisions in a Case of Multiple Sclerosis - Putri Nadya Syahidah; Setyorini Irianti; Aih Cahyani (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Pregnancy in women with multiple sclerosis (MS) complicated by fetal anomalies presents immediate clinical and ethical challenges. MS, a chronic autoimmune disorder of the central nervous system, commonly affects women of reproductive age and necessitates balancing maternal disease stability with fetal safety. This case report, based on retrospective clinical data and a narrative literature review, highlights the complexities of managing such pregnancies. A 27-year-old G5P2A2 woman at 19 weeks' gestation with relapsing-remitting MS, previously treated with methotrexate during the first trimester, was referred for high-risk care following the detection of a membranous ventricular septal defect (VSD) via fetal echocardiography. Despite teratogenic concerns, the pregnancy was continued under multidisciplinary management involving obstetrics, neurology, rheumatology, and fetomaternal cardiology. The outcome was a preterm delivery of a neonate with VSD requiring specialized follow-up, while the mother remained clinically stable without MS relapse. This case underscores the ethical tensions between maternal autonomy, beneficence, non-maleficence, and justice, particularly in navigating reproductive choices amid uncertain neonatal outcomes. Shared decision-making, supported by multidisciplinary counseling, proved essential in guiding care. Clinicians managing high-risk pregnancies in women with autoimmune disease must integrate ethical principles within collaborative frameworks to optimize outcomes for both mother and child. Keywords: High-Risk Pregnancy, Congenital Anomaly, Ethical Dilemmas, Patient Autonomy, Shared Decision-Making.